PENGARUH PERSEPSI DUKUNGAN ORGANISASI TERHADAP KINERJA GURU DENGAN DIMEDIASI OLEH PERILAKU KERJA INOVATIF (Studi pada Guru SMA Negeri 1 Klaten) - Oktavia Ria Winola; Edy Raharja (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The purpose of this study was to determine the direction of Perceived organizational support on teacher performance with innovative work behavior as a mediating variable for teachers at SMA Negeri 1 Klaten. The independent variables in this study are Perceived organizational support, teacher performance as the dependent variable, and innovative work behavior as mediating variables. This research is in the form of mixed research using a questionnaire as a data collection method. The population used was SMA Negeri 1 Klaten teachers, with a total sample of 56 teachers. The data analysis method uses Structural Equation Modeling (SEM) through the SmartPLS version 3.2.9 software application. The results of this study indicate that Perceived Organizational Support has a positive and significant effect on Teacher Performance. Perceived Organizational Support have a positive and insignificant effect on Innovative Work Behavior. Innovative work behavior has a positive and significant effect on teacher performance. This study also shows that Innovative Work Behavior cannot be an Intervening variable on the influence between Perceived Organizational Support and Teacher Performance.